Iron induces two distinct Ca2+ signalling cascades in astrocytes - Wenzheng Guan (Nature Portfolio, 2021)
Wenzheng Guan and Maosheng Xia et al. use a combination of pharmacological, genetic, and calcium imaging approaches to describe two mechanisms of iron-induced astrocytic calcium signaling. Altogether, these results suggest that astrocytes may act as a barrier to excessive iron in the brain, thereby improving our understanding of the role of astrocytes in normal neurodevelopment.